2020
DOI: 10.3390/en13236220
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Building Parameter Uncertainty in District Heating for Optimal Control of Network Flexibility

Abstract: Network flexibility is the use of the thermal capacity of water that is contained in the district heating network pipes to store energy and shift the heat load in time. Through optimal control, this network flexibility can aid in applications such as peak shaving and operational heat pump optimisation. Yet, optimal control requires perfect predictions and complete knowledge of the system characteristics. In reality, this is not the case and uncertainties exist. To obtain insight into the importance of these un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…DH Networks provide flexibility by using the thermal capacity of water that is contained in the district heating network pipes to store energy and shift the heat load in time [21]. They are predicted to provide a substantial contribution towards future carbon neutral heating in the UK, particularly to urban areas [22].…”
Section: Technology Reviewmentioning
confidence: 99%
“…DH Networks provide flexibility by using the thermal capacity of water that is contained in the district heating network pipes to store energy and shift the heat load in time [21]. They are predicted to provide a substantial contribution towards future carbon neutral heating in the UK, particularly to urban areas [22].…”
Section: Technology Reviewmentioning
confidence: 99%
“…The parts of a DH system that need to be controlled entail the heat supply units and the heat distribution network. However, controlling the heating system of the buildings in the DH network can further improve the overall system performance, since the thermal inertia of these buildings offers a significant amount of flexibility for the MPC [4]. Therefore, the buildings' physics should be included in the controller model such that this flexibility can be exploited by the MPC.…”
Section: Introductionmentioning
confidence: 99%
“…SH discomfort and electrical energy use for the period 28-31 January (winter) and 27-30 April (spring) for RBC and MPC 4. …”
mentioning
confidence: 99%
“…It used a modified Optimal Power Flow (OPF) to evaluate the feasibility of the flexibility provision [16]. Furthermore, case studies have been performed to investigate the impact of the aggregation of heat pumps and uncertainties inherent in forecasts and building parameters [17,18]. It is revealed that it is beneficial to include domestic hot water (DHW) demand within the optimization model to deal with the high unpredictability of the DHW consumption.…”
Section: Introductionmentioning
confidence: 99%